A revised and improved version of the Northern Wheatear (Oenanthe oenanthe) transcriptome - Frias Soler, Roberto Carlos; Villarín Pildaín, Lilian; Wink, Michael; Bairlein, Franz (Diversity, 2021)
This work presents an updated and more complete version of the transcriptome of a long-distance migrant, the Northern Wheatear (Oenanthe oenanthe). The improved transcriptome was produced from the independent mRNA sequencing of adipose tissue, brain, intestines, liver, skin, and muscle tissues sampled during the autumnal migratory season. This new transcriptome has better sequencing coverage and is more representative of the species’ migratory phenotype. We assembled 20,248 transcripts grouped into 16,430 genes, from which 78% were successfully annotated. All the standard assembly quality parameters were improved in the second transcriptome version.
Gesehen am 19.05.2021